Magnetic-field induced multi-step transitions in ferromagnetic spin-crossover solids within the BEG model - OKE, Djidjoho Toussaint; NDIAYE, Mamadou; HONTINFINDE, FÉLIX; BOUKHEDDADEN, Kamel (My University, 2021)
We study by means of the 2D Blume–Emery–Griffiths (BEG) spin-1 model, spin-crossover (SCO) and prussian blue analogs (PBAs) solids. In this model, the spin states, which can be high-spin (HS) or low-spin (LS), interact magnetically and elastically with their nearest neighbors. To account for the volume change, accompanying the spin transition phenomenon, all interactions through the lattice are assumed as temperature-dependent. In addition, the system is subject to a variable magnetic field lifting the degeneracy in the HS state. A stochastic cooperative dynamics of this BEG-like Hamiltonian, describing the equilibrium and nonequilibrium properties of ferromagnetic spin-crossover solids, is derived from the Glauber approach, with appropriate Arrhenius microscopic transition rates. The model generates under the magnetic field, sigmoidal relaxation and a hysteresis phenomenon of the HS fraction, as well as multistep behavior of the magnetization. These behaviors open the way to new route of multi-stable systems, desired in multi-byte electronics.
Keywords: SCO materials; BEG-like spin-1 Hamiltonian; equilibrium and non-equilibrium properties; master equation; sigmoidal relaxation and hysteresis phenomenon; multistep spin transition